Respuesta :

Answer:

6(7a+2) (a-2)

Step-by-step explanation:

Add and subtract the second term to the expression and Factor by grouping.

I'm not really sure but I hope this is the answer

9514 1404 393

Answer:

  6(a -2)(7a +2)

Step-by-step explanation:

Removing a common factor of 6 can make the quadratic factors easier to find.

  = 6(7a^2 -12a -4)

We want to find factors of (7)(-4) that have a total of -12. It doesn't take much search to see they are (-14)(2), so the expression can be written as ...

  = 6(7a^2 -14a +2a -4) = 6((7a^2 -14a) +(2a -4)) . . . . rewrite 'a' term; group pairs

  = 6((7a(a -2) +2(a -2)) . . . . factor pair groups

  = 6(a -2)(7a +2) . . . . . . . . finish factoring